2017
DOI: 10.1002/ptr.5989
|View full text |Cite
|
Sign up to set email alerts
|

Myricetin attenuated LPS induced cardiac injury in vivo and in vitro

Abstract: Sepsis induced myocardial dysfunction (SIMD) is a common complication and leads to an increased mortality. SIMD is closely related to inflammation and oxidative stress. Myricetin exhibits strong capacities of anti-inflammation and anti-oxidative stress, but its pharmacological effects for lipopolysaccharide (LPS) induced cardiac injury remains undefined. This study aimed to explore whether myricetin was efficient to alleviate SIMD in mice and neonatal rat cardiomyocytes injury. Mice administrated with myriceti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 35 publications
2
44
0
Order By: Relevance
“…In the present study, we found a significantly prohibitive function of myricetin on the phosphorylated expression of p65 and IκBα. Our results appeared to be consistent with a previous study that myricetin significantly attenuated LPS-induced IκB degradation, and nuclear translocation of p65 and NF-κB DNA-binding activity in LPS-treated macrophages [17, 28]. Accordingly, the expression of cytokines is regulated.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the present study, we found a significantly prohibitive function of myricetin on the phosphorylated expression of p65 and IκBα. Our results appeared to be consistent with a previous study that myricetin significantly attenuated LPS-induced IκB degradation, and nuclear translocation of p65 and NF-κB DNA-binding activity in LPS-treated macrophages [17, 28]. Accordingly, the expression of cytokines is regulated.…”
Section: Discussionsupporting
confidence: 93%
“…We found that myricetin exhibited pro-proliferative and anti-apoptotic effects in LPS-induced inflammatory injury of cardiomyocytes. Analogously, its cardio-protective function has been proved in ischemia/reperfusion rat model and sepsis-induced myocardial dysfunction mice model [17, 21], while a few epidemiological and clinical findings have been reported in the benefits of myricetin on myocarditis. Most probably, it is due to its poor water solubility and oral bioavailability that hinder its potential use [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peritoneal macrophages were prepared in our laboratory from adult C57/B6 male mice according to our previously reported methods [ 17 ]. Macrophages were cultured in RPMI 160 culture medium containing 15% heat inactivated fetal bovine serum for 1 h. The supernatant was removed, and the adherent cells were peritoneal macrophages.…”
Section: Methodsmentioning
confidence: 99%
“…Myricetin also prevented over expression of induced nitric oxide synthase (iNOS) and reduction of oxidoreductase (SOD and GPx) activity. Besides, Myricetin treatment could attenuate production of inflammatory cytokines of peritoneal macrophages stimulated with LPS in vitro [55].…”
Section: Cardioprotective Activitymentioning
confidence: 97%